1940
DOI: 10.3181/00379727-45-11749
|View full text |Cite
|
Sign up to set email alerts
|

Complement Titer of Blood of the Newborn

Abstract: During the course of studies on the complement content of human blood, we noted that the cord blood of the newborn infants consistently was of a lower titer than that of adults. We, therefore, determined simultaneously the complement titer of a series of newborn (cord) bloods and of the mother's blood taken at the time of delivery.The titration was made according to the method outlined by Ecker, et nl.' The serum was diluted 1 to 15 and a series of tubes starting with 0.01 cc of the diluted serum and increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

1943
1943
1997
1997

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…The results of this study have demonstrated conclusively that the serum complement activity of normal newborn infants is approximately one half that of normal adults and mothers at term. Similar results have been reported by Solling [lo], Wasserman and Alberts [13] and Traub [ll].…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study have demonstrated conclusively that the serum complement activity of normal newborn infants is approximately one half that of normal adults and mothers at term. Similar results have been reported by Solling [lo], Wasserman and Alberts [13] and Traub [ll].…”
Section: Discussionsupporting
confidence: 91%
“…Similar results have been reported by Solling [10], Wasserman and Alberts [13] and Traub [11 ]. I t has been our experience that serum complement levels determined in normal newborns during the first several days of .…”
Section: Discussionsupporting
confidence: 80%
“…F ireman et al [22] found decreased levels of total hemolytic complement (CH50) and C3, C4, and C5 in newborns compared to the paired maternal sera; in the LBW infants, the levels were lower in proportion to the degree of gestational immaturity. In 1937, Solling [15] demonstrated that cord blood C?I50 was lower than that of the paired maternal blood, an ob servation confirmed by Wasserman and Alberts [16] a few years later. T raub [17] also confirmed these observations and showed that post-partum maternal sera had higher complement levels than sera from normal control women, and that no correlation existed between the complement levels in the maternal and newborn sera.…”
Section: Introductionmentioning
confidence: 85%
“…In LBW infants there is, in ad dition, decreased placental passage of IgG globulin, rendering these infants deficient in all 3 major immune globulins [4], Yet, this antibody deficiency state offers only a partial explanation for the newborn's sluggish defense system inasmuch as agammaglob ulinémie patients, despite lower antibody and y-globulin levels, show a much more vigorous response to infection. For this reason investi gation of other components of the immune system in newborns has been undertaken, including studies of delayed hypersensitivity [5], lo cal antibody response [6], white cell function [7][8][9][10][11][12][13] and opsonic [12,13] and complement (C) activity of the serum [13][14][15][16][17][18][19][20][21][22]. In general these show increasing degrees of impairment with increasing imma turity.…”
Section: Introductionmentioning
confidence: 99%